Analisis Kinerja DPKAD Kota Semarang Dalam Pengelolaan Pajak Restoran di Kota Semarang - Fahriz Rachmad Rinaldi; Yuwanto . (Journal of Politic and Government Studies, 2019)
This study tries to describe (1) trying the method used by the City of Semarang DPKAD in setting restaurant tax targets (2) increasing the factors that encourage and improve the performance of Semarang City DPKAD in collecting and increasing the potential for restaurant tax to increase benefits for Semarang City PAD (3) using Semarang city tax collection to increase the contribution of Semarang City PAD. The method used in this study is a mixed method, which is a study involving previous research, namely qualitative research and quantitative research. This restaurant tax management covers aspects, the planning process carried out by the Field of Data Collection, Determination, and Billing (P3) and can not be separated from the Planning Field, organizing process, organizing activities, grouping activities, and delegating authority in accordance with work plans and functions , as well as allocating resources, the process of mobilizing employees carried out through meetings and coordination, the supervision process carried out by looking at some of the restaurant tax obligations provided by the field officers when carrying out their duties. Meanwhile, the driving factor for restaurant tax management in the city of Semarang, namely the implementation of object data and taxpayers, the availability of regulations that are the legal basis, the availability of sufficient budget and human resources; While the inhibiting factor is the level of public awareness that is still low, sanctions for restaurants that do not need to ask for help and the amount of reduction in the field to collect data on restaurant taxpayers. Keywords: performance analysis, restaurant tax, semarang